Comparison of sampling and culture methods for the recovery of yeast from hospital surfaces - Allison R. Eberly; Alyssa M. Valencia; Kate Peacock; David McDonald; Tiffany Hink; Carleigh Samuels; Lucy Vogt; Yao-Peng Xue; Maggie Newberry; Caroline A. O’Neil; Gautam Dantas; Jennie H. Kwon (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract